Higher education personnel’s perceptions about telepresence robots - Leoste, Janika; Virkus, Sirje; Talisainen, Aleksei; Tammemäe, Kalle; Kangur, Katrin; Petriashvili, Izabella (Frontiers in Robotics and AI, 2022)
The interest towards using telepresence robots in a variety of educational contexts is growing, as they have a great potential to enhance the educational experience of remote learners and provide support for teachers. This paper describes a study, examining the perception of Georgian university personnel about the use of telepresence robots in education. This exploratory research aimed to obtain evidence-based information on how the personnel (16 persons) from eight Georgian universities perceived the telepresence robots’ role in enhancing learning and teaching, and what challenges, benefits, opportunities, weaknesses and threats would characterise these robots. The results of the study revealed that the university personnel perceived telepresence robots to have a great potential to enhance educational activities. In addition, the participants indicated the major challenges, benefits, opportunities, weaknesses and threats, regarding integrating telepresence robotics into the teaching and learning in Georgia. Recommendations for future research are also presented.